Comparison of Ethanol Production from three Different Tuber Plants (Manihot esculenta, Ipomoea batata and Dioscorea Spp) - Zakari, Muhammad Saminu; Wazimtu, Rebecca Paul; Emmanuel, Sarki Salvation (Darul Yasin Al Sys, 2025)
In recent years, the annual energy consumption from petroleum sources has increased many folds resulting not only in continuous depletion of limited fossil fuel stocks but also a cause of concern for the safer, better and greener environment. Further, the high prices of fossil fuel have led to an energy crisis in both developing and developed countries that are oil dependent. Following these challenges, there is need to find alternative sources of producing energy. This study aimed at comparison of ethanol production from three different tuber plants (Manihot Esculenta, Ipomoea Batata and Dioscorea SPP). The cassava, sweet potato and yam peels were collected from the market premises of Jalingo Local Government Area, Taraba State. The collected samples were taken to a convenient place where they were sorted. The peels of cassava, sweet potato and yam were separately sorted to have mainly the peels for drying. The drying was carried out in open air which lasted for a week. The well dried samples were then milled using a hammer mill, Mortar and pestle which reduced the cassava, sweet potato and yam peels to very small particle sizes and weighed. To 10 g of the powdered wort, distilled water was added, mashed and filtered. Yeast and malt were added to the filtered wort and allowed to stand for three (3) days for fermentation. After fermentation, the fermented wort was distilled to collect a colourless liquid as the distillate. This distillate was neutral to litmus test, soluble in water and indicated the presence of alcohol by Ester, Sodium Metal, Iodoform and Lucas Tests. The result compared from 3 samples showed that cassava peels produced the highest ethanol concentration (6.25) followed by yam peels (6.13) while the minimum ethanol yield was obtained from sweet potato peels (5.01) at temperature 78.40C and PH 7.2 after 72 hours of fermentation. This work has shown that cassava, sweet potato and yam peels which are considered a non-valuable waste are suitable raw materials and could be efficiently utilized for the production of ethanol.